Crimean-Congo hemorrhagic fever in children - (:unkn) unknown (ELSEVIER, 2010)
Background: Crimean-Congo hemorrhagic fever (CCHF) virus causes a severe disease in humans with a mortality up to 30%. In Turkey there has been an increase in the number of cases during years since 2002. Humans of all ages living in endemic areas, especially those who are working as shepherds and toddlers, have high risk of acquiring CCHF. Objectives: The epidemiological, clinical, and laboratory characteristics of the children, who were diagnosed as Crimean-Congo hemorrhagic fever (CCHF) were described. Study design: The children infected with CCHF virus between April 2008 and October 2009, and hospitalised in Ankara Diskapi Children's and Research Hospital were included. Results: Laboratory diagnosis was set by detection of CCHF IgM antibodies and/or genetic detection of CCHF virus. Thirtyone cases included to the study, and all were from the northeastern Anatolia and the southern parts of Black sea region. The mean age was 9.45 +/- 4.9 years, the proportion of females was 38.7%. The majority (87%) of the cases had the history of tick bite. There was no fatal case. All the patients had the history of fever. Malaise, tonsillopharyngitis, nausea-vomiting, headache, diarrhea, myalgia and rash were the most common symptoms. The mean AST and ALT levels on the admission were 116 (range 25-389) and 61 (range 8-180) U/L respectively. The mean platelet count on admission was 125,000/mm(3), and the lowest was 23,000/mm(3). The mean of the lowest white blood cell count was 2353/mm(3) and the mean of the highest lactate dehydrogenase was 861 IU/L. Conclusions: The clinical course of CCHF among children seems to be milder than in adults. Tonsillopharyngitis is a common symptom among children with CCHF. (C) 2010 Elsevier B. V. All rights reserved.
Keywords: Crimean-Congo hemorrhagic fever; Children; Ribavirin; ACUTE RESPIRATORY SYNDROME; CLINICAL-FEATURES; RISK-FACTORS; RIBAVIRIN; OUTBREAK; TURKEY